When we were very young - Milne, A. A. (Alan Alexander) 1882-1956.; Shepard, Ernest H. 1879-1976. (Ernest Howard). (New York Dell Publishing, 1942)
A collection of poems reflecting the experiences of a little English boy growing up in the early part of the twentieth century.
Originally published: New York : E.P. Dutton, 1924.
Keywords: Children's poetry, English; English poetry